E-Book Mobile Application: A Case of Kabale University Mukombe Library, Uganda - Clare, Ninsiima; Patricia, Kyomugisha (East African Journal of Information Technology, 2022)
Globally, many academic e-books are available in user-friendly forms like PDF and HTML that can be accessed on laptops, iPads, and smartphones, even though some e-books require a special e-book reader. However, university students find it difficult to access e-books because some of the university libraries have few computers that hold the downloaded e-books, which are stored in a folder, and little effort has been made as a result; there is low usage of e-books. The project’s goal was to investigate how e-book applications work and how students at Kabale University can access e-books via mobile phone or tablet. The objectives of the project were to investigate the existing e-books application, design and develop the e-books application, and test and validate the developed application that enables students at Kabale University to access e-books simultaneously. The literature review helped me read a number of pieces of literature about e-book applications. They were information sources about the E-books application such as the internet, books, journals, and newspapers, among others. The use of existing information from the library helped to develop a model to predict the E-book application and testing of the application using Android smartphones. It was concluded that the implementation of the e-book’s application was done using Android to enable users to access the books on their mobile phones or tablets. The study recommends that the administrator of the system should be taken through the tasks in order to be able to upload books ready for the application.